Determinants of Prosperity in Nepal: Analysis of Nepal Living Standard Survey Data 2010/11 - Karki, Ram Bahadur (Humanities and Social Sciences Journal, 2022)
To give the answer of whether and to what extent educational and health status determines prosperity, this paper explains the relative effect of prosperity among the level of education and health status as the capability of an individual. The variables are qualitative in nature so the standard statistical methods, chi-square, and logistic regression techniques have been applied to identify the extent to which the factors influence the probability of both households and individuals being prosperous. For this purpose, analyzing the data from Nepal Living Standard Survey (NLSS, 2010/11), I argue that educational achievement as an individual capability is a major determining factor of prosperity rather than other variables. In conclusion, a higher level of education means a higher level of prosperity.